2021
DOI: 10.1038/s41598-021-94249-7
|View full text |Cite
|
Sign up to set email alerts
|

Photocontrolled apoptosis induction using precursor miR-664a and an RNA carrier-conjugated with photosensitizer

Abstract: Methods to spatially induce apoptosis are useful for cancer therapy. To control the induction of apoptosis, methods using light, such as photochemical internalization (PCI), have been developed. We hypothesized that photoinduced delivery of microRNAs (miRNAs) that regulate apoptosis could spatially induce apoptosis. In this study, we identified pre-miR-664a as a novel apoptosis-inducing miRNA via mitochondrial apoptotic pathway. Further, we demonstrated the utility of photoinduced cytosolic dispersion of RNA (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
2
0
1
Order By: Relevance
“…We previously investigated the mechanism of heat stress response in cancer cells and found that thermal sensitizers can enhance the cell-killing effect of heat stress by inhibiting the formation of stress-induced nuclear granules to downregulate the expression of heat shock proteins [ 48 ]. In the future, the modification of THP-MNPs with drug molecules, such as thermal sensitizers and proapoptotic peptides/miRNAs [ 49 , 50 ], is expected to improve cancer treatment efficiency. This study anticipates further progress towards in vivo studies to validate the therapeutic effects of THP-MNPs on magnetic hyperthermia.…”
Section: Discussionmentioning
confidence: 99%
“…We previously investigated the mechanism of heat stress response in cancer cells and found that thermal sensitizers can enhance the cell-killing effect of heat stress by inhibiting the formation of stress-induced nuclear granules to downregulate the expression of heat shock proteins [ 48 ]. In the future, the modification of THP-MNPs with drug molecules, such as thermal sensitizers and proapoptotic peptides/miRNAs [ 49 , 50 ], is expected to improve cancer treatment efficiency. This study anticipates further progress towards in vivo studies to validate the therapeutic effects of THP-MNPs on magnetic hyperthermia.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously demonstrated PCDR-mediated, light-dependent RNA delivery using several TatU1A-photosensitizer molecules with photosensitizers such as Alexa633 (λex ~ 633 nm; red) and DY750 (λex ~ 750 nm; near-infrared) 13 , 23 . The PCDR method enables the delivery of a precursor miRNA in addition to shRNAs and photoinduced apoptosis mediated by the miRNA 18 . The PCDR method is an efficient approach to the spatial regulation of gene expression 23 , and temporally limited RNA upregulation 19 .…”
Section: Discussionmentioning
confidence: 99%
“…1. 緒言 各種キャリアを用いた動物細胞内へのタンパク質や核 酸などの生体分子(キャリアに対する積み荷分子)の導 入は,エンドサイトーシスを経由するケースが多く,そ の場合,キャリア/積み荷複合体がエンドソームに閉じ込 められてしまう問題がしばしば起こる 1,2) .この問題の解 決法の 1 つとして,光増感剤と光を用いてエンドソーム にトラップされた物質をエンドソームから脱出させ細胞 質内に導入する方法(photochemical internalization:PCI 法)が知られている [3][4][5] .PCI 法は,細胞に取り込まれ, エンドソームにトラップされた膜不透過性分子の光依存 的細胞質内送達法として開発され,核酸やタンパク質, 薬剤の細胞質内デリバリーに応用されてきた 6,7) .この方 法は,送達したい分子のエンドサイトーシスが起こると き,光増感剤も同時にエンドソームに局在するように設 計されている.ここで,光を照射すると光増感剤により 活性酸素種(主に一重項酸素)が生成し,一重項酸素に よるエンドソーム膜の不安定化に基づいて,エンドソー ム内の分子が細胞質内に放出される 3) . 本研究では,PCI に基づく光誘導 RNA 細胞質内導入法 (photoinduced cytosolic dispersion of RNA:PCDR 法)を用 いる 2) .この手法は,細胞透過性ペプチドの一種である Tat と U1A RNA 結合タンパク質と光増感剤(PS)複合体 (TatU1A-PS)により,short hairpin RNA(shRNA)や pre-miRNA などの RNA を光依存的に細胞質内に導入する方 法である 8,9)…”
unclassified